Letter from the Managers of the Fair for the Church of the Redeemer to James Curtis Booth - Church of the Redeemer (Bryn Mawr, Pa.) (1860)
The Managers of the Fair for the Church of the Redeemer write to James Curtis Booth (1810-1888) concerning a donation of religious tracts by a Mr. MacDuff to be sold at their fair in aid of the Parsonage Fund.
Keywords: Booth, James Curtis, 1810-1888; Charity